Prestimulation of CD2 confers resistance to HIV-1 latent infection in blood resting CD4 T cells - Sijia He (Elsevier, 2021)
Summary: HIV-1 infects blood CD4 T cells through the use of CD4 and CXCR4 or CCR5 receptors, which can be targeted through blocking viral binding to CD4/CXCR4/CCR5 or virus-cell fusion. Here we describe a novel mechanism by which HIV-1 nuclear entry can also be blocked through targeting a non-entry receptor, CD2. Cluster of differentiation 2 (CD2) is an adhesion molecule highly expressed on human blood CD4, particularly, memory CD4 T cells. We found that CD2 ligation with its cell-free ligand LFA-3 or anti-CD2 antibodies rendered blood resting CD4 T cells highly resistant to HIV-1 infection. We further demonstrate that mechanistically, CD2 binding initiates competitive signaling leading to cofilin activation and localized actin polymerization around CD2, which spatially inhibits HIV-1-initiated local actin polymerization needed for viral nuclear migration. Our study identifies CD2 as a novel target to block HIV-1 infection of blood resting T cells.